LepNet: The Lepidoptera of North America Network - Seltmann, Katja C.; Cobb, Neil S.; Gall, Lawrence F.; Bartlett, Charles R.; Basham, M. Anne; Betancourt, Isabelle; Bills, Christy; Brandt, Benjamin; Brown, Richard L.; Bundy, Charles; Caterino, Michael S.; Chapman, Caitlin; et al. (Zootaxa, 2017)
The Lepidoptera of North America Network, or LepNet, is a digitization effort recently launched to mobilize biodiversity data from 3 million specimens of butterflies and moths in United States natural history collections (http://www.lep-net.org/). LepNet was initially conceived as a North American effort but the project seeks collaborations with museums and other organizations worldwide. The overall goal is to transform Lepidoptera specimen data into readily available digital formats to foster global research in taxonomy, ecology and evolutionary biology.